2020
DOI: 10.21668/health.risk/2020.1.01.eng
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic determinants and potential for growth in life expectancy of the population in the Russian Federation taking into account regional differentiation

Abstract: The current work supplements the results obtained in previous research on a relation between leading parameters of living conditions and life expectancy of the RF population; it dwells on the results obtained via analyzing a role played by sanitary and epidemiologic determinants. A sanitary-epidemiologic situation in certain RF regions is unfavorable and it makes our research truly vital; it is also necessary to work out and implement activities aimed at eliminating or minimizing adverse environmental factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The moderator also mentioned another study focusing on sanitaryepidemiological determinants of life expectancy growth in Perm region. These determinants include providing people with qualitative drinking water and raising safety of certain foods (meat, milk, fish, and bread) [46]. A correlation between the aforementioned housingrelated and other everyday problems and growing infection risks is obvious for experts.…”
mentioning
confidence: 99%
“…The moderator also mentioned another study focusing on sanitaryepidemiological determinants of life expectancy growth in Perm region. These determinants include providing people with qualitative drinking water and raising safety of certain foods (meat, milk, fish, and bread) [46]. A correlation between the aforementioned housingrelated and other everyday problems and growing infection risks is obvious for experts.…”
mentioning
confidence: 99%
“…Участники дискуссии обратили внимание на социологический опрос российских пенсионеров, проведенный весной 2020 г., согласно которому из тех, кто проживает в частном секторе, более чем у 30 % нет постоянного доступа к горячей воде и теплому туалету, также 30 % опрошенных свидетельствовали об отсутствии лифтов, удобств ванных комнат и туалетов [30]. Модератор отметил исследование санитарно-эпидемиологических детерминант роста продолжительности жизни населения в Пермском крае, к которым отнесены обеспечение качественной питьевой водой и повышение безопасности отдельных продуктов питания (мясо, молоко, рыба, хлеб) [46]. Связь перечисленных жилищных и житейских проблем с увеличением инфекционных рисков здоровью очевидна для специалистов.…”
unclassified
“…And we should stress that only people with the best functional parameters were employed at that production since it involved exposure to a lot of adverse occupational factors; all workers had profound medical examinations prior to being employed. Obviously, should there be improvements in all the set of social-and hygienic factors including occupational ones, it will have a positive effect on overall workers' life expectancy [5].…”
mentioning
confidence: 99%
“…Hygienic science unavoidably has to examine and substantiate effects produced by adverse hygienic factors under long-term exposure regulated by relevant standards and documents. Accomplished studies revealed that in case all significant sanitary-hygienic factors were improved, physical factors held the second rank place as per their contribution made into life expectancy [5].…”
mentioning
confidence: 99%